First principles study of structural, optical, and electronic properties of zinc mercury chalcogenides. (February 2015) - Murtaza, G.; Ullah, Naeem; Rauf, Abdur; Khenata, R.; Bin Omran, S.; Sajjad, M.; Waheed, A.
Abstract: First-principles calculations using the full potential linearized augmented plane wave method within the framework of density functional theory are performed to investigate the compositional dependence of the structural, electronic and optical properties of Zn1− x Hg x E (E=S, Se, Te). It is observed that except the lattice constant, the variation of the bulk modulus and the band gap versus mercury composition does not obey Vegard׳s law. The alloys at all concentrations have direct band gap ( Γ − Γ ) which decreases with increasing the concentration of Hg. Optical properties like complex dielectric function and reflectivity are discussed comprehensively. The properties of these materials such as the direct band gap and high absorption in the infrared to ultraviolet regions demonstrate the significant optical activity of these materials.